Interdisciplinarity From Below - Pante, Michael D. (Archīum Ateneo, 2024)
Interdisciplinarity is one of the key catchphrases that define the ongoing educational reform in the Philippines. Through the K-12 basic education curriculum and the revamped tertiary-level general education curriculum, bureaucrats and their partners in the academe seek to equip students with knowledge and skills that will allow them to think and act beyond their chosen field. Such an edge supposedly affords graduates a competitive advantage in a highly globalized labor market. Nonetheless, one must not be carried away by the hype; interdisciplinarity, especially this version imposed from above, still has to be interrogated. For one, lost in the state-directed discourse of interdisciplinarity is the emancipatory tradition arising from epistemological movements that question methodological and conceptual conventions. In the discipline of history, one such epistemological movement—with “movement” deployed here in its broadest sense—is the push toward crafting a “history from below.” Foregrounding diversity rather than orthodoxy, this historiographical turn has sought to give voice to the voiceless. In the Philippines, the nineteenth-century ilustrados’ conception of the nascent field of Philippine studies and the social histories that broke new ground starting in the 1970s best represent this progressive knowledge–power nexus. These examples demonstrate that interdisciplinarity, for it to be beneficial, should not be the goal itself but a means to an end. Without substantial changes emanating “from below,” especially among teachers and students from the huge number of educational institutions neglected by the state, the promise of interdisciplinarity that the Philippine government is peddling is nothing but the production of fantasy.